INNOVATION ECOSYSTEM AS A KEY FACTOR OF REGION ECONOMIC GROWTH - Bulat A. Akhmadeev; Nikita A. Moiseev (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article studies the concept of innovation ecosystem by drawing an analogy between innovation and natural ecosystems. The authors identify basic elements of innovation ecosystems and their relations at different stage of innovation life cycle. They put forward the concept of developing the innovation component of the region at the expense of continuous support of start-ups through governmental subsidies and raising commercial capital to fundamental science. This process is carried out by introduction of demonstration system and technologies development, as well as organization of return finance and information links in the structure of innovation ecosystem. A conclusion was drawn that in certain conditions the system from balanced state can pass over to growth.